The Principle and Controls of the Distributed Generation of the Renewable Energy sources - Nasrullayev, Seymur (ADA University, 2023)
The integration of renewable energy sources and load represents challenges for the economical operation of the grid, while also giving rise to power quality issues. Extensive research has been undertaken in order to mitigate the difficulties associated with the resilience of the grid, principle, and control system of the integration of RES, and power quality interruptions. Moreover, there is a big emphasis placed on the topics of voltage variation and reactive power regulation. The interdependence of voltage and reactive power necessitates the utilization of a shared instrument for their resolution. The notion of volt-var control (VVC) has been extensively discussed in the existing literature, as thoroughly examined in this review work. The primary objective of this work is to analyze methodologies for advanced VVC applications. Furthermore, it offers the reader an in-depth overview of optimization of the distributed generations, encompassing the minimization of loss, voltage deviation, energy consumption, and operating with minimal control variables.
Keywords: Renewable energy sources--Integration--Power grid; Voltage regulation--Power systems; Reactive power--Control; Distributed generation (Electric power)--Optimization; Power grids--Economic aspects; Energy consumption--Optimization; Energy systems--Control and optimization; IT and Engineering